Nerve growth cones isolated from fetal rat brain. IV. Preparation of a membrane subfraction and identification of a membrane glycoprotein expressed on sprouting neurons (The Rockefeller University Press, 1985)
This study describes the preparation of a membrane subfraction from isolated nerve growth cone particles (GCPs) (see Pfenninger, K. H., L. Ellis, M. P. Johnson, L. B. Friedman, and S. Somlo, 1983, Cell, 35:573- 584) and the identification in this fraction of a glycoprotein expressed during neurite growth. While approximately 40 major polypeptides are visible in Coomassie Blue-stained SDS polyacrylamide gels of pelleted (partially disrupted) GCPs, a salt-washed membrane fraction prepared from lysed, detergent-permeabilized GCPs contains only 14% of this protein and has an unusually simple polypeptide pattern of seven major bands. Monoclonal antibodies have been generated to GCP membranes isolated from fetal rat brain. These antibodies have been screened differentially with synaptosomes from adult rat brain in order to identify those which recognize antigens expressed selectively during neurite growth. One such antibody (termed 5B4) recognizes a developmentally regulated membrane glycoprotein that is enriched in GCP membranes and expressed in fetal neurons sprouting in vitro. The 5B4 antigen in fetal brain migrates in SDS polyacrylamide gels as a diffuse band of approximately 185-255 kD, is rich in sialic acid, and consists of a small family of isoelectric variants. Freezing-thawing and neuraminidase digestion result in the cleavage of the native antigen into two new species migrating diffusely around 200 and 160 kD. Prolonged neuraminidase digestion sharpens these bands at about 180 and 135 kD, respectively. In the mature brain, antibody 5B4 recognizes a sparse polypeptide migrating at approximately 140 kD. As shown in the following paper (Wallis, I., L. Ellis, K. Suh, and K. H. Pfenninger, 1985, J. Cell Biol., 101:1990-1998), the fetal antigen is specifically associated with regions of neuronal sprouting and, therefore, can be used as a molecular marker of neurite growth.